A Late Cretaceous dinosaur and crocodyliform faunal association–based on isolate teeth and osteoderms–at Cerro Fortaleza Formation (Campanian-Maastrichtian) type locality, Santa Cruz, Argentina - Paulina Carabajal, Ariana (2021)
The Late Cretaceous dinosaur record in southern South America has been improved recently; particularly with findings from Chorrillo and Cerro Fortaleza formations, both bearing ankylosaur remains, a clade that was not previously recorded in the Austral Basin. The dinosaur fauna of the type locality of Cerro Fortaleza Formation is known from -and biased to- large-sized sauropod remains and a single described taxon, the titanosaur Dreadnoughtus schrani. Here, we report the taxonomic composition of a site preserving thirteen isolated teeth and several osteoderms belonging to three dinosaur clades (Abelisauridae, Titanosauria, and Nodosauridae), and at least one clade of notosuchian crocodyliforms (Peirosauridae). They come from sediments positioned at the mid-section of the Cerro Fortaleza Formation, which is Campanian-Maastrichtian in age, adding valuable information to the abundance and biodiversity of this Cretaceous ecosystem. Since non-titanosaur dinosaur bones are almost absent in the locality, the teeth presented here provide a window onto the archosaur biodiversity of the Late Cretaceous in southern Patagonia. The nodosaurid tooth and small armor ossicles represent the first record of ankylosaurs for this stratigraphic unit. The peirosaurid material also represents the most austral record of the clade in South America.